2016
DOI: 10.1016/j.janxdis.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

The From Survivor to Thriver program: RCT of an online therapist-facilitated program for rape-related PTSD

Abstract: This study evaluated the efficacy of the From Survivor to Thriver program, an interactive, online therapist-facilitated cognitive-behavioral program for rape-related PTSD. Eighty-seven college women with rape-related PTSD were randomized to complete the interactive program (n = 46) or a psycho-educational self-help website (n = 41). Both programs led to large reductions in interview-assessed PTSD at post-treatment (interactive d = 2.22, psycho-educational d = 1.10), which were maintained at three month follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(92 citation statements)
references
References 69 publications
(112 reference statements)
2
89
0
Order By: Relevance
“…Only one study reported regular face‐to‐face therapist guidance , with the remainder of studies that reported therapist guidance indicating that it was delivered over the phone or via email/messaging service. Duration of treatment ranged from four to fourteen weeks . Five of the included studies evaluated trauma‐focused interventions; the remainder were non‐trauma‐focused.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one study reported regular face‐to‐face therapist guidance , with the remainder of studies that reported therapist guidance indicating that it was delivered over the phone or via email/messaging service. Duration of treatment ranged from four to fourteen weeks . Five of the included studies evaluated trauma‐focused interventions; the remainder were non‐trauma‐focused.…”
Section: Resultsmentioning
confidence: 99%
“…Studies were conducted in the United States (six studies) , Australia (one study) , Iraq (one study) , Sweden (one study) and the United Kingdom (one study) . Studies included individuals traumatised by military combat ; living in a war zone (one study) ; and rape (one study) . The remainder of the studies included individuals traumatised by various traumatic events .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies compared i-CBT with a waitlist control group, treatment as usual (TAU) or minimal attention control group (k = 8), and with an i-non-CBT psychological intervention (k = 2). Studies were conducted in five countries: Australia (k = 1) (Spence et al, 2011); Iraq (k = 1) (Knaevelsrud, Brand, Lange, Ruwaard, & Wagner, 2015); Sweden (k = 1) (Ivarsson et al, 2014); UK (k = 1) (Lewis et al, 2017); and USA (k = 6) (Engel et al, 2015;Krupnick et al, 2017;Kuhn et al, 2017;Littleton, Grills, Kline, Schoemann, & Dodd, 2016, Litz et al, 2007Miner et al, 2016). Three studies recruited in clinical settings via clinician referrals (Engel et al, 2015;Krupnick et al, 2017;Lewis et al, 2017), these studies also recruited via media, website and promotional material advertising, which was the method used by the remaining seven studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Trauma type varied, with three studies concerning service members with military and terrorist-related trauma (Engel et al, 2015;Krupnick et al, 2017;Litz et al, 2007), and one study concerning civilians with warrelated trauma (Knaevelsrud et al, 2015), reporting moderate to severe PTSD symptoms, overall. Six studies reported individuals with fairly consistent PTSD severities of mild to moderate level, one study concerning rape trauma (Littleton et al, 2016), the others including a range of traumatic events taking place in the community (Ivarsson et al, 2014;Kuhn et al, 2017;Lewis et al, 2017;Miner et al, 2016;Spence et al, 2011).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%